Implications of Peptidyl Arginine Deiminase 4 gene transcription and polymorphisms in susceptibility to rheumatoid arthritis in an Iranian population - Zahra Bagheri-Hosseinabadi; Mohammad Reza Mirzaei; Ozrasadat Esmaeili; Fatemeh Asadi; Hassan Ahmadinia; Banafshe Shamsoddini; Mitra Abbasifard (BMC, 2023)
Abstract Background Peptidyl arginine deiminase 4 (PADI4) has been implicated in Rheumatoid arthritis (RA) pathogenesis. Here we aimed to evaluate the association of PADI4 gene rs11203367 and rs1748033 single nucleotide polymorphisms (SNPs) with RA proneness. Methods The mRNA expression of PADI4 was determined in the whole blood samples. The genotyping of PADI4 polymorphisms was conducted using allelic discrimination TaqMan genotyping Real-time PCR. Results The alleles and genotypes of rs11203367 polymorphism were not associated with susceptibility to RA risk. The T allele (OR = 1.58, 95%CI: 1.21-2.04, P = 0.0005), TT genotype (OR = 2.79, 95%CI: 1.53-5.06, P = 0.0007), TC genotype (OR = 1.52, 95%CI: 1.04-2.23, P = 0.0291), dominant (OR = 1.72, 95%CI: 1.19-2.47, P = 0.0034) and recessive (OR = 2.19, 95%CI: 1.25-3.82, P = 0.0057) models of rs1748033 SNP were associated with higher risk of RA. There was a significant upregulation of PADI4 mRNA in the RA patients compared to controls. mRNA expression of PADI4 had significantly positive correlation with anti-CCP level (r = 0.37, P = 0.041), RF level (r = 0.39, P = 0.037), and CRP level (r = 0.39, P = 0.024). Conclusion PADI4 gene rs1748033 SNP was associated with increased RA risk. This polymorphism might affect the RA pathogenesis regardless of impressing the levels of PADI-4 in serum.